2017
DOI: 10.1002/tox.22413
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane attenuates di-N-butylphthalate-induced reproductive damage in pubertal mice: Involvement of the Nrf2-antioxidant system

Abstract: di-N-butylphthalate (DBP) is a ubiquitous environmental pollutant used for plastic coating and in the cosmetics industry. It has toxic effects on body health, especially the male reproductive system. Here, we investigated the effects of DBP on the male reproductive system of pubertal mice and explored the protective role of sulforaphane (SFN). The results showed that DBP significantly reduced the anogenital distance, testicular weight, sperm count and motility, and plasma and testicular testosterone levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…Oxygen free radicals cause damage to cells through both peroxidation of polyunsaturated fatty acids in biofilms and the decomposition products of lipid hydroperoxides. Therefore, the amount of MDA is measured to reflect the extent of lipid peroxidation in the body and indirectly reflect the extent of cellular damage (Jiang et al, 2017). Our study confirmed that GSH-Px and MDA are directly related to oxidative aging in mice and that LP-KSFY02 can exert its role in inhibiting oxidative aging by increasing the activity of GSH-Px and lowering the amount of MDA.…”
Section: Discussionsupporting
confidence: 74%
“…Oxygen free radicals cause damage to cells through both peroxidation of polyunsaturated fatty acids in biofilms and the decomposition products of lipid hydroperoxides. Therefore, the amount of MDA is measured to reflect the extent of lipid peroxidation in the body and indirectly reflect the extent of cellular damage (Jiang et al, 2017). Our study confirmed that GSH-Px and MDA are directly related to oxidative aging in mice and that LP-KSFY02 can exert its role in inhibiting oxidative aging by increasing the activity of GSH-Px and lowering the amount of MDA.…”
Section: Discussionsupporting
confidence: 74%
“…Nuclear factor-erythroid 2 p45-related factor 2 (Nrf2), a basic leucine zipper redox-sensitive transcription factor, is a master regulator of cell's antioxidant response via binding antioxidant response element (ARE) [ 13 ]. Our group has demonstrated that deficiency of Nrf2 caused deteriorated antioxidant capacity in a mouse model of dibutyl phthalate- (DBP-) induced oxidative stress [ 14 ]. And we have found that Nrf2 and its downstream target genes were upregulated in injured kidney tissue induced by ischemia and reperfusion (I/R).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of γ‐GCS is instrumental in the antioxidant role of GSH (Obrador et al, 2014). NQO1, which is downstream of Nrf2, triggers an antioxidant reaction and plays the role of Nrf2 (Jiang et al., 2017). In this study, ITPL upregulated the expression of oxidized Nrf2 by enhancing the expression levels of HO‐1, γ‐GCS, and NQO1, thereby protecting the mice and alleviating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%